Analisis faktor-faktor yang memengaruhi indeks kualitas lingkungan hidup di Kabupaten Bekasi - Nurul Iswari; Arief Budi Kusuma (Pusat Penelitian Lingkungan Hidup, IPB (PPLH-IPB) dan Program Studi Pengelolaan Sumberdaya Alam dan Lingkungan, IPB (PS. PSL, SPs. IPB), 2022)
Environmental quality index is needed to describe the initial indication of the environmental conditions of an area in a certain period. Bekasi district, the largest industrial area in Indonesia and Southeast Asia, faces environmental damage that can threaten the quality of human life. Local governments need the determination of the environmental quality index of Bekasi Regency to get quick conclusions from environmental conditions in Bekasi Regency. Many factors can affect the environmental quality index in Bekasi Regency, both direct driving factors and supporting factors. Twenty-four assessment instruments must be assessed by nine expert panelists from several regional agencies. The Delphi method was used to obtain consensus from two rounds of interviews with expert panelists. Changes in land cover, type of land cover, household solid waste pollution, household liquid waste pollution, industrial air pollution, and industrial liquid waste pollution are the direct driving factors that most influence the environmental quality index in Bekasi Regency. Meanwhile, population growth and population migration are the supporting factors that most influence the environmental quality index in Bekasi Regency.